Non-Tariff Measures Affecting EU Exports Evidence From a Complaints-Inventory - Walkenhorst, Peter (OECD Economics Department Working Papers, 2003)
Evaluating the importance of non-tariff measures (NTMs) affecting imports remains a major challenge. This study reports evidence on the prevalence of NTMs based on an inventory of business complaints. This data source has the advantage of drawing on experiences of economic agents that are directly involved in trading activities, of containing information on "behind the border measures", and of covering procedural aspects of NTMs. The results suggest that natural resource based industries, such as agriculture and food, mining, and textiles, are most strongly affected by NTMs relative to their export volumes. Certification procedures, quantity control measures, and technical regulations are the types of NTM most frequently complained about. Complaints about domestic governance practices, such as impediments related to government procurement, investment restrictions, or insufficient intellectual property rights protection account for almost a third of all NTM observations and are in ...